Analysis of Traditional Training Methods in Human Resource Development: A Literature Review of the Use of Experiential Learning Methods for Employees - Muhamad Gherdianto Aziz Sadewo; Nurindah Sari; Ahyakudin A (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to analyze traditional training methods in human resource management development and to examine the relevance of experiential learning as an alternative approach to improving employee competence and performance. This study employs a literature review using a qualitative descriptive approach. Data were obtained from journals, books, and scientific articles relevant to traditional training, experiential learning, and human resource development. Data were analyzed using content analysis by identifying, comparing, and interpreting findings from various sources. The results indicate that traditional training methods remain relevant as they provide employees with structured conceptual understanding and foundational knowledge. However, these methods have limitations in fostering active participation and direct application in the workplace. Experiential learning can complement traditional training because it emphasizes direct experience, reflection, conceptual understanding, and active application. The implications of this research suggest that organizations need to integrate traditional training with experiential learning so that employee development programs become more effective, participatory, and practical.